The 21st century parent : multicultural parent engagement leadership strategies handbook - Johnson, Mary (Emerald Publishing Limited : Information Age Publishing, 2012)
The 21st Century Parent emphatically remind us that the missing ingredient in closing the gaps in achievement is heaping measure of parent engagement and community. This is one-of-a kind book, even the most savvy expert will find novel advice and useful tools, sample school practices, and strategies. The book is outstanding resources recognizing and building upon asset that Parents and communities bring in creating partnership for children's school success.Packed with tips for parents, principals and teachers, resource tools, and an invaluable guide for engaging parents, The 21st Century Parent reveals how to build strong collaborative relationships and offers practical advice for improving interactions between parents and teachers, from insuring that parents are constructive and inclusive to navigating the complex issues surrounding diversity in the classroom and how parents can be transformative change agents for their children and their schools.Written with candor, clarity, and humor, 21st Century Parent is essential reading for teachers, parents on the front lines in public schools, and administrators and policy makers at all levels.
Keywords: Parent-U-Turn (Organization); Education -- Parent participation -- California -- Los Angeles -- Handbooks, manuals, etc.; School improvement programs -- California -- Los Angeles.; Multiculturalism -- California -- Los Angeles.; Education -- Administration -- General.; Teaching staff.; Educational administration and organization.; elektronické knihy; electronic books